Outcomes of Corneal Cross-Linking Correlate With Cone-Specific Lysyl Oxidase Expression in Patients With Keratoconus. Issue 3 (March 2018) - Shetty, Rohit; Rajiv Kumar, Nimisha; Pahuja, Natasha; Deshmukh, Rashmi; Vunnava, KrishnaPoojita; Abilash, Valsala Gopalakrishnan; Sinha Roy, Abhijit; Ghosh, Arkasubhra
Abstract : Purpose: To evaluate the correlation of visual and keratometry outcomes after corneal cross-linking (CXL) in patients with keratoconus with cone epithelium–specific gene expression levels. Methods: Corneal epithelium was obtained from 35 eyes that underwent accelerated CXL (KXLII, 9 mW/cm 2 for 10 min). Using corneal topography, epithelium over the cone and periphery was obtained separately from each subject. The ratio of gene expression for lysyl oxidase (LOX), matrix metalloproteinase 9 (MMP9), bone morphogenic protein 7, tissue inhibitor of metalloproteinase 1, collagen, type I, alpha 1, and collagen, type IV, alpha 1 (COL IVA1) from the cone and peripheral cornea was correlated with the outcome of cross-linking surgery. Patients were assessed for visual acuity, keratometry, refraction, and corneal densitometry before and 6 months after surgery. Based on the change in corneal flattening indicated by ΔKmax, the outcomes were classified as a higher response or lower response. Results: Reduction in keratometric indices correlated with improved spherical equivalent after CXL. Preoperative levels of cone-specific LOX expression in cases with a higher response were significant ( P = 0.001). COL IVA1, bone morphogenic protein 7, and tissue inhibitor of metalloproteinase 1 gene expressions were reduced in the cones of the subjects with a lower response. MMP9 levels were relatively lower in cases with a higher response compared with those with a lower response. Conclusions: Our study demonstrates that preoperative levels of molecular factors such as LOX, MMP9, and COL IVA1 aid in understanding CXL outcomes at the tissue level. Abstract : Supplemental Digital Content is Available in the Text.